SISTEM PENDUKUNG KEPUTUSAN PENENTUAN TINGKAT KEPUASAN PELAYANAN MASYARAKAT DI KANTOR CAMAT PERBAUNGAN KABUPATEN SERDANG BEDAGAI DENGAN METODE TOPSIS - Ridho, Irhamir; Marbun, Murni (STMIK Kaputama, 2019)
Perbaungan Subdistrict Office of Serdang Bedagai Regency is a service office for the community, services are all forms of activities carried out by employees to help the community in the fields of administration, social welfare, government and other public services. Good services in the form of improving employee performance in serving the community at the Perbaungan District Office of Serdang Bedagai District, to determine the level of community service satisfaction at the Perbaungan District Office, a Decision Support System (SPK) is needed. This Decision Support System uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method and the criteria consist of: Hospitality, Responsibility, Speed, Continuity, Attendance and Response, the system was built with Visual Basic Programming language 2010. The results of the satisfaction level research community service to the service of Perbaungan Sub-district Head Office of Serdang Bedagai Regency, from 6 employees it is known that Asniwati Br. Karo is an employee who serves the community with a very satisfied level of satisfaction.